2012
DOI: 10.3109/09638288.2011.645114
|View full text |Cite
|
Sign up to set email alerts
|

“Governed by the pain”: narratives of fibromyalgia

Abstract: The narrative is characterized by a lack of movement and resolution, with participants engaged in an enduring struggle against the challenges of FM. Psychological approaches that facilitate this ongoing adjustment process may prove beneficial in FM treatment and rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 28 publications
4
36
0
1
Order By: Relevance
“…Fibromyalgia as an illness experience requires understanding and action, from the person at the centre of the experience, and those who surround and support this individual (McMahon et al . ). While there is a growing South African body of literature related to the subject, most studies are concerned with clinical aspects, such as chronic pain diagnosis and treatment (Namane , Raff et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fibromyalgia as an illness experience requires understanding and action, from the person at the centre of the experience, and those who surround and support this individual (McMahon et al . ). While there is a growing South African body of literature related to the subject, most studies are concerned with clinical aspects, such as chronic pain diagnosis and treatment (Namane , Raff et al .…”
Section: Introductionmentioning
confidence: 97%
“…A person with fibromyalgia, their practitioners, institutions, workplaces and social networks are continuously challenged to prove the existence of the condition as a serious and chronic illness (McMahon et al . , Chen ). This paper aims to assess the impact of contestation related to fibromyalgia as a diagnosis on an individual's ability to articulate their experience to family and support networks.…”
Section: Introductionmentioning
confidence: 99%
“…3 makes sense when it is placed in relation to the explanations found in the literature on the adaptation process, which FM sufferers must face (44). Said process can be set out by a division of the following phases: explaining previous personal experience to FM; being given a diagnosis and accepting it; negative feelings towards oneself upon the manifestation of suffering; feeling trapped in ones’ own body; adaptation to FM; and continuing to fight for a better quality of life (45). …”
Section: Discussionmentioning
confidence: 99%
“…Studies [18,19] have shown that peer support is important. However, research has also shown that for women with FM, the invisibility of their condition leads to mistrust and a lack of understanding from others, including friends, family, and healthcare personnel [1,8,10]. Such disbelief and lack of understanding increase the experience of uncertainty and contribute to social withdrawal and isolation [6,7].…”
Section: Introductionmentioning
confidence: 91%
“…Living with FM means living with a long-term pain syndrome that has a considerable impact on daily life [1][2][3][4][5][6][7][8]. Several studies [7,9,10] have shown that people with invisible chronic illnesses, such as FM, lack support.…”
Section: Introductionmentioning
confidence: 97%